2008
DOI: 10.1021/ja800434r
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Studies on Carbon−Carbon Reductive Elimination from Bis(hydrocarbyl) Complexes of (PCP)Ir

Abstract: The reductive elimination of carbon-carbon bonds is one of the most fundamentally and synthetically important reaction steps in organometallic chemistry, yet relatively little is understood about the factors that govern the kinetics of this reaction. C-C elimination from complexes with the common d (6) six-coordinate configuration generally proceeds via prior ligand loss, which greatly complicates any attempt to directly measure the rates of the specific elimination step. We report the synthesis of a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
79
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 65 publications
10
79
0
Order By: Relevance
“…The Ir-CMe bond length in 1 + was 2.10 Å, which was comparable to the value that was found in the X-ray structure 2 and the related pincer Ir(III)-methyl complexes. 5 The Ir-CPh bond length in 2 + was 2.07 Å, which was also comparable to the value that was found in the related pincer Ir(III)-phenyl complexes. 5 The phenyl ring in 2 + was vertical to the plane that was defined by Ir and its pincer ligand, and therefore, the hydrogen atom that was attached to Ir was also in the same plane.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The Ir-CMe bond length in 1 + was 2.10 Å, which was comparable to the value that was found in the X-ray structure 2 and the related pincer Ir(III)-methyl complexes. 5 The Ir-CPh bond length in 2 + was 2.07 Å, which was also comparable to the value that was found in the related pincer Ir(III)-phenyl complexes. 5 The phenyl ring in 2 + was vertical to the plane that was defined by Ir and its pincer ligand, and therefore, the hydrogen atom that was attached to Ir was also in the same plane.…”
supporting
confidence: 81%
“…5 The Ir-CPh bond length in 2 + was 2.07 Å, which was also comparable to the value that was found in the related pincer Ir(III)-phenyl complexes. 5 The phenyl ring in 2 + was vertical to the plane that was defined by Ir and its pincer ligand, and therefore, the hydrogen atom that was attached to Ir was also in the same plane. The Ir-H bond lengths were 1.54 Å in In 1-σ + , the Ir-H bond length was elongated to 1.83 Å, and the Ir-CMe bond was lengthened to 1.48 Å.…”
supporting
confidence: 81%
“…2.26 Å versus 3.85 Å) and, accordingly, the calculated C-C activation pathway involves a fully perpendicular approach. As evidenced by the separate rotamers formed from C-H activation of biphenylene with tBu PCPIr, as well as its reluctance to reductively eliminate C (Ph) -C bonds [42], rotation of phenyl groups bound to tBu PCPIr is severely hindered. By extension, in the double C-H activation of biphenyl it is likely that the initial C-H activation occurs with the un-activated Ph ring syn to the hydride since rotation from the anti-addition product to form 1 would be restricted (Scheme 4).…”
Section: Reactions With Biphenyl Phenanthrene and Fluorenonementioning
confidence: 99%
“…Goldman, Krogh-Jespersen, et al previously showed that, for Ar−X (X = Me, Ph, CHCH 2 , CCH) RE from five-coordinate (PCP)Ir(Ar)(X), the aryl group must be oriented "face-on" toward X in the transition state. 29 The steric influence of the phosphines in the ground state of (PCP)Ir(Ar)(X) favors the "side-on" orientation of the aryl group with respect to X, and the necessary rotation of the aryl can be a considerable component of the activation barrier. This situation can be contrasted with the typical (R 3 P) n Pd(Ar)(X) (n = 1, 2) intermediates, where the steric bulk of the phosphines favors "face-on" orientation of the aryl with respect to X in the ground state and encourages faster RE.…”
Section: Scheme 4 Proposed Catalytic Cycle For the Coupling Of Arylmentioning
confidence: 99%